PFAS-transport från mark till grundvatten - En studie om transportpåverkande faktorer vid brandövningsplatsen på Arlanda - Johansson,Elin (2025)
PFAS contamination has been identified at numerous sites worldwide, particularly at firefigh-ting training facilities. Firefighting foams, Aqueous film forming foam (AFFF), used at these facilities often contain PFAS as their active substance. The aim of this study was to examine factors that influence transport of eleven different substances of PFAS. Furthermore the study aimed to see how long time PFOS is transported in the unsaturated zone in a future per-spective. The study is based on measured concentrations of PFOS at Arlanda Airport´s fire-fighting training site. Methods included a literature review and data compilation from field samples of PFAS11 (the eleven most common PFAS elements) in the soil and PFOS in groundwater. Based on measured levels of PFOS, modeling was performed on the transport of the substances in the unsaturated zone using the software Hydrus 1D. The results show that the highest levels of PFAS11 is found in the upper one meter of the soil. Factors that in-fluence the transport of PFAS11 is the carbon chain lengths, the geology, the level of water saturation in the soil and the amount of organic carbon in the soil. The modeling showed that it takes 170–500 years for PFOS to leach from the soil at the sample points in Arlanda depen-ding on whether a Kd of 3,5 l/kg or 10 l/kg is applied in the model. A lower Kd-value leads to a higher leeching of PFOS into the groundwater during a shorter amount of time than would be the case with a higher Kd. This makes it particularly important to know the exact Kd -value for the substance in that environment. It is thus, important to take continuous local samples of the soil, groundwater and surface water to monitor the spread of PFAS.